Preliminary safety evaluation of n-butanol from the collagen extraction process and of collagen extract from Oreochromis niloticus (tilapia) skin oriented for dermocosmetics - Sánchez Tuesta, Linda Cristina (2021)
Authors are very thankful to CONCYTECFONDECYT, process E041-01 (Contract number 123-2018-FONDECYT-BM-IADT/AV), Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) Process 305250/2019-1, Coordenação de Aperfeiçoamento de Pessoal de Nível Superior-Brasil (CAPES) Finance Code 001 and Programa Nacional de Pós-Doutorado (PNPD).